High serum levels of leucine-rich α-2 glycoprotein 1 (LRG-1) are associated with poor survival in patients with early breast cancer - Göbel, Andy; Rachner, Tilman Daniel; Hoffmann, Oliver; Klotz, Daniel Martin; Kasimir-Bauer, Sabine; Kimmig, Rainer; Hofbauer, Lorenz; Bittner, Ann-Kathrin (Archives of gynecology and obstetrics, 2024)
Leucine-rich α-2 glycoprotein 1 (LRG-1) is a secreted glycoprotein that is mainly produced in the liver. Elevated levels of LRG-1 are found in a multitude of pathological conditions including eye diseases, diabetes, infections, autoimmune diseases, and cancer. In patients with early breast cancer (BC), high intratumoral LRG-1 protein expression levels are associated with reduced survival. In this study, we assessed serum levels of LRG-1 in patients with early BC and investigated its correlation with the presence of disseminated tumor cells (DTCs) in the bone marrow and survival outcomes.
Online veröffentlicht am 28. Februar 2024
Gesehen am 04.11.2024